Establishing Diagnostic Reference Levels for Chest X-ray Diagnosis - Pitskhelauri, Ana; Esvanjia, Nino; Kutateladze, Lasha (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Modern medicine is unthinkable without radiological diagnostics. Medical diagnostics involves high-resolution visualization of organs and tissues, which is associated with certain radiation risks. This is precisely what has led to the determination of the Diagnostic Reference Level (DRL) becoming a topical issue, which is required by both international and Georgian legislation for national X-ray diagnostic protocols for Georgia. The definition of DRL ensures patient safety, quality assurance, economic benefit, regulatory compliance, and technological advancement. In order to optimize radiation safety for patients in Georgia, we have piloted the definition of DRL for the X-ray diagnostic protocol. In particular, a tool was created in the MATLAB environment, using which it became possible to determine the DRL for a specific radiological procedure - the chest radiological protocol. Using the created tool, many chest radiographs (visual material) were processed and the results were obtained.